Left sided Amyand’s hernia - Unver, Mutlu (Baishideng Publishing Group Co., Limited, 2013)
The presence of the appendix in an inguinal hernia sac has been referred to as Amyand’s hernia. Vermiform appendix located in an external hernia sac is not an uncommon condition, and the incidence of these cases is approximately 1%. In Amyand’s hernias, appendices are frequently found in the hernia sac; but an incarceration particularly on the left side is a very unusual sight. In this report we present 32-year-old male with Amyand’s hernia on the left side.